NZ J Ecol 2017
DOI: 10.20417/nzjecol.41.7
|View full text |Cite
|
Sign up to set email alerts
|

Assessing and comparing population densities and indices of skinks under three predator management regimes

Abstract: Introduced mammalian predators threaten populations of endemic New Zealand skinks. Their effects on skink populations have been not often quantified on the mainland and are known primarily from skink population increases on islands from which mammals have been eradicated. Estimating skink population density with capture-recapture trapping is time-consuming and costly. Counting skinks in artificial retreats in specific weather conditions may be a useful and relatively quick way to index population density, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Models in which g 0 was also an additive function of mouse weight and/or a behavioural response to capture were also tested. Two alternative types of behavioural responses to capture (Efford 2016) were considered: b, a permanent response in which an animal's probability of capture increased (a trap-happy response) or decreased (trap-shy) after its first capture; and bk, a trap-specific permanent response in which an animal became trap-happy or trap-shy in relation to a particular trap (Royle et al 2011;Wilson et al 2017). Table 2.…”
Section: Study Sitementioning
confidence: 99%
“…Models in which g 0 was also an additive function of mouse weight and/or a behavioural response to capture were also tested. Two alternative types of behavioural responses to capture (Efford 2016) were considered: b, a permanent response in which an animal's probability of capture increased (a trap-happy response) or decreased (trap-shy) after its first capture; and bk, a trap-specific permanent response in which an animal became trap-happy or trap-shy in relation to a particular trap (Royle et al 2011;Wilson et al 2017). Table 2.…”
Section: Study Sitementioning
confidence: 99%
“…A suite of introduced mammals such as rats (kiore, Rattus exulans, R. norvegicus, and R. rattus), mustelids (stoats (Mustela erminea), ferrets (M. furo), and weasels (M. nivalis), mice (Mus musculus), along with some domesticated animals (e.g. dogs (Canis familiaris), cats (Felis catus)) prey on native reptiles (Hoare et al, 2007;Salo et al, 2007;Wilson et al, 2017). Predator control has increased in the country since studies reported a positive relationship between the eradication of introduced predators on offshore islands and improved survivability and reproduction of native species (Whitaker, 1973;Towns, 1991;Towns, 1995;Monks et al, 2014;Parkes et al, 2014;Jones et al, 2016).…”
Section: New Zealand Lizardsmentioning
confidence: 99%
“…Individual dispersal from release site is reported strongest in the first weeks to months following release and is a key determinant of success (Tuberville et al, 2005 (Eifler & Eifler, 1999;Wilson et al, 2017)).…”
Section: Recapture Locationmentioning
confidence: 99%
See 2 more Smart Citations